THE RELATIONSHIP BETWEEN STUDENTS' PERCEPTIONS OF BUILDING MAINTENANCE ENGINEERING SKILLS COMPETENCIES AND POST-GRADUATE ORIENTATION AT SMKN 1 PALANGKA RAYA - Septian Adji Nugroho; Samuel Layang; Petrisly Perkasa (Jurusan Pendidikan Teknologi Dan Kejuruan, 2024)
The perception of each individual is different and there are many aspects that influence a person's perception of anything, including determining the ideals or targets to be achieved. The orientation or direction of students' plans after graduating from vocational school will lead to work, continuing education or entrepreneurship. The student's post-graduate orientation or plans will be related to the student's perception of Skill Competency during their studies. The purpose of this research is to determine students' perceptions regarding Building Maintenance Engineering Skills Competencies at SMKN 1 Palangka Raya, students' plans after graduating from SMKN 1 Palangka Raya, and to describe the magnitude of the relationship between students' perceptions and orientation after graduating from SMKN 1 Palangka Raya. The research method used is the correlational descriptive method. The research instrument used a questionnaire, both for student perception variables and orientation after graduating from vocational school. The population in this research is students of classes X and XI in Building Maintenance Engineering and the entire population will be used as samples for testing. The findings of this research are: (1) students' perceptions of Building Maintenance Engineering Skills Competency have high criteria; (2) orientation after graduating from vocational school is in the high category and tends to lead to work and continuing after graduation; and (3) The influence of the relationship between student perceptions regarding Building Maintenance Engineering skills competency and post-graduate orientation at SMK Negeri 1 Palangka Raya. It could be said that there is no significant influence between student perceptions and post-graduate orientation, because on average students answered that their goals after graduation.